Efecto de la planta madre en el establecimiento in vitro del Guanabano - Rivero M, G. del C.=700 1 Ramirez V, M. del C.; De Sierralta, S.L.
(En, Es)
ilus., 7 ref.
Keywords: ANNONA MURICATA; MICROPROPAGACION; PLANTA DONANTE; VENEZUELA; AGRONOMIA TROPICAL